Curve Numbers as affected by soil conservation treatments in small watersheds in lower Himalayas of north-west India - CHANDEL, SUMITA; HADDA, M. S.; MAHAL3, AMRIT KAUR (Journal of Soil and Water Conservation, 2022)
Curve numbers (CNs) were computed and evaluated employing different measures of central tendency in estimating runoff through CN method in the watersheds of lower Himalayas of northwest India. The watersheds treated over the untreated demonstrated lower CNs, both for Patiala-Ki-Rao and Saleran watersheds. However, the asymptotic computed average reference CNs and R2 were equal in magnitude. The ordered rainfall-runoff storms through Curve Number-Precipitation relationships demonstrated different shapes and behaviours such as complacent and standard in the watershed (s). The soil moisture retention improved by difference in magnitude of 10%, using the initial interception to soil moisture retention parameter (Ia/S) ratio of 0.3 over 0.2. The NRCS and standard asymptotic method better performed at estimating CNs in treated watersheds at both the locations and untreated watersheds of Saleran only. The study further suggested exploring more research by adjusting CNs with changes in slope steepness in the watersheds area.